2011
DOI: 10.1021/ef2004909
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Acid, Alkali, and Steam Explosion Pretreatments on Characteristics of Bio-Oil Produced from Pinewood

Abstract: Bio-oil produced from pinewood by fast pyrolysis has the potential to be a valuable substitute for fossil fuels. Pretreatment prior to the fast pyrolysis process has been shown to alter the structure and chemical composition of biomass. To determine the influence of biomass pretreatments on bio-oil produced during fast pyrolysis, we tested three pretreatment methods: dilute acid, dilute alkali, and steam explosion. Bio-oils were produced from untreated and pretreated pinewood feedstocks in an auger reactor at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(35 citation statements)
references
References 50 publications
2
33
0
Order By: Relevance
“…The results presented here correspond well to the results of Wang et al (2011) who studied the effect of acid, alkali and steam explosion pretreatments. Wang et al (2011) reported that more bio-oil was formed in the pyrolysis of the acid treated samples (63%), while less bio-oil was formed from the steam exploded (44%) and alkaline treated (49%) biomass compared to the untreated one (54%). The char yields were about the same ($19%) for the untreated, steam exploded and acid treated samples, while the alkaline treatment resulted in 24% of char.…”
Section: Pyrolysis Mass Balancesupporting
confidence: 89%
“…The results presented here correspond well to the results of Wang et al (2011) who studied the effect of acid, alkali and steam explosion pretreatments. Wang et al (2011) reported that more bio-oil was formed in the pyrolysis of the acid treated samples (63%), while less bio-oil was formed from the steam exploded (44%) and alkaline treated (49%) biomass compared to the untreated one (54%). The char yields were about the same ($19%) for the untreated, steam exploded and acid treated samples, while the alkaline treatment resulted in 24% of char.…”
Section: Pyrolysis Mass Balancesupporting
confidence: 89%
“…It was concluded that SAS could solubilize the hemicellulosic fraction of the orange peel and soften the lignin structure. Therefore, the acid soaked sample had a loose and porous structure (Wang et al, 2011). More significantly, the loose and porous structure could result in an increase in high pressure steam permeation into the cell tissues of orange peel, which could form more powerful explosive decompression.…”
Section: Effect Of Sulfuric Acid Concentration On the Extraction Yielmentioning
confidence: 99%
“…VAC accounted for 50.0%. Phenolics are the product of lignin degradation during the pyrolysis, while furans are the decomposition product of cellulose and hemicellulose (Wang et al 2011;Le Roux et al 2015;Deshmukh et al 2015). These compounds can be further processed to biochemicals and biopolymers that are important feedstocks for the chemical and plastic industries.…”
Section: Characterization Of Bio-oil Non-condensable Gas and Bio-charmentioning
confidence: 99%